2009
DOI: 10.1074/jbc.m807505200
|View full text |Cite
|
Sign up to set email alerts
|

Rab1 Guanine Nucleotide Exchange Factor SidM Is a Major Phosphatidylinositol 4-Phosphate-binding Effector Protein of Legionella pneumophila

Abstract: The causative agent of Legionnaires disease, Legionella pneumophila, forms a replicative vacuole in phagocytes by means of the intracellular multiplication/defective organelle trafficking (Icm/Dot) type IV secretion system and translocated effector proteins, some of which subvert host GTP and phosphoinositide (PI) metabolism. The Icm/Dot substrate SidC anchors to the membrane of Legionella-containing vacuoles (LCVs) by specifically binding to phosphatidylinositol 4-phosphate (PtdIns(4)P). Using a nonbiased scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
270
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(276 citation statements)
references
References 62 publications
(73 reference statements)
3
270
1
1
Order By: Relevance
“…However, PI(3)P at late endosomes/lysosomes is expected to be further phosphorylated to PI(3,5)P 2 , by the activity of the PI 5-kinase PIKfyve. Similarly to Legionella effectors, CvpB uses PIs for membrane anchoring, apparently using a nonconventional lipid-binding domain as previously reported for the Legionella effectors SidC and SidM (42,43). Similarly to the Salmonella effector SopB, Coxiella CvpB triggers an increase in PI(3)P levels of infected cells to favor the biogenesis of a spacious replicative compartment (40).…”
Section: Discussionmentioning
confidence: 89%
“…However, PI(3)P at late endosomes/lysosomes is expected to be further phosphorylated to PI(3,5)P 2 , by the activity of the PI 5-kinase PIKfyve. Similarly to Legionella effectors, CvpB uses PIs for membrane anchoring, apparently using a nonconventional lipid-binding domain as previously reported for the Legionella effectors SidC and SidM (42,43). Similarly to the Salmonella effector SopB, Coxiella CvpB triggers an increase in PI(3)P levels of infected cells to favor the biogenesis of a spacious replicative compartment (40).…”
Section: Discussionmentioning
confidence: 89%
“…Intriguingly, PI(4,5)P 2 may be further converted to PI(4)P by the host PI-5-phosphatase OCRL (20). Thus, one plausible hypothesis is that SidF plays a role in the establishment of LCVs with a lipid composition enriched in PI(4)P. It has been suggested that PI(4)P provides specific anchors on the LCV for Legionella effectors, such as SidC/SdcA (18) and SidM(DrrA) (31). Through binding to PI(4)P, these effectors presumably facilitate the fusion of ERderived vesicles with the LCV.…”
Section: Sidf Facilitates the Anchoring Of Effector Proteins To Bactementioning
confidence: 99%
“…Later it was demonstrated that it contains only GEF activity in a central domain containing residues 340 -533, but that no active displacement (GDI displacement factor activity) occurs (15). The C-terminal domain of the protein was reported to bind phosphatidylinositol-4-phosphate with high affinity (16,17), and the N-terminal domain was shown to be an adenylyltransferase catalyzing the covalent attachment of an AMP moiety to Tyr 77 in the switch II region of Rab1 (18). It was shown that the modifications has only small effects on DrrA-mediated nucleotide exchange, whereas catalysis by the GAPs LepB and TBC1D20 is strongly inhibited.…”
mentioning
confidence: 99%